Baseline sensitivity of European Zymoseptoria tritici populations to the complex III respiration inhibitor fenpicoxamid. Issue 11 (28th July 2022) - Kildea, Steven; Hellin, Pierre; Heick, Thies M.; Hutton, Fiona
Abstract: BACKGROUND: Fenpicoxamid is a recently developed fungicide belonging to the quinone inside inhibitor (QiI) group. This is the first fungicide within this group to be active against the Zymoseptoria tritici, which causes Septoria tritici blotch on wheat. The occurrence of pre‐existing resistance mechanisms was monitored, using sensitivity assays and Illumina sequencing, in Z. tritici populations sampled in multiple European countries before the introduction of fenpicoxamid. RESULTS: Although differences in sensitivity to all three fungicides tested (fenpicoxamid, fentin chloride and pyraclostrobin) existed between the isolate collections, no alterations associated with QiI resistance were detected. Among the isolates, a range in sensitivity to fenpicoxamid was observed (ratio between most sensitive/least sensitive = 53.1), with differences between the most extreme isolates when tested in planta following limited fenpicoxamid treatment. Sensitivity assays using fentin chloride suggest some of the observed differences in fenpicoxamid sensitivity are associated with multi‐drug resistance. Detailed monitoring of the wider European population using Illumina‐based partial sequencing of the Z. tritici also only detected the presence of G143A, with differences in frequencies of this alteration observed across the region. CONCLUSIONS: This study provides a baseline sensitivity for European Z. tritici populations to fenpicoxamid. Target‐site resistance appears to be limited or non‐existing in European Z. tritici populations prior to the introduction of fenpicoxamid. Non‐target site resistance mechanisms exist, but their impact in the field is predicted to be limited. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : No cytochrome b alterations associated with fenpicoxamid resistance were detected in European Zymoseptoria tritici populations sampled in 2019 prior to its launch. By contrast, the alteration G143A, which confers quinone inside inhibitor (QoI) resistance was found to dominate almost all populations in Western Europe. Differences in the in vitro sensitivity to fenpicoxamid were detected between the different country collections; however, limited impacts were observed in in planta sensitivity under controlled conditions.